A Review of Polymer Laser Sintering and Fused Deposition Modelling of Polymers - Fredrick Mwania; Maina Maringa; Jacobus van der Walt (Advances in Polymer Technology)
Currently, the world is undergoing the fourth industrial revolution, also referred to as Industry 4.0, which is characterised by a set of new technological advances in the industrial and production sectors. Additive manufacturing (AM) is considered an essential factor in this new era because of its ability to process a wide spectra of materials, produce customised products, promote sustainability and develop intricate components which are unachievable using conventional manufacturing techniques. The field of AM is rapidly evolving and has seen unprecedented uptake in many industries. Different types of AM technologies have been developed over the last three decades to process different materials, such as polymers, composites, metals, ceramics and alloys. Both industry and academia have made a considerable effort to investigate the use of AM technologies to print different types of polymers because of the possibility to reach new markets. This comprehensive review focuses on polymer laser sintering (PLS) and fused deposition modelling (FDM), which are the most commonly employed AM methods for polymers. This review outlines the processes, process parameters, available commercial polymeric materials, benefits, challenges, and applications of the two technologies. PLS and FDM are multifactorial processes that produce final components whose quality is subject to the process parameters. This review, therefore, delves into the different process parameters for the two technologies and their impacts. The article also lists the available commercial polymeric materials, for each of the methods, to assist researchers and industries to select most suitable materials based on their processability and characteristics. A detailed discussion of applications of the two technologies is outlined in this review. The study provides a comprehensive detail of the benefits and challenges of PLS and FDM. Last, the study also outlines the future works for the two techniques.